Immigration and political distrust in Europe: a comparative longitudinal study. Issue 2 (14th March 2020) - Jeannet, Anne-Marie
ABSTRACT: European countries have witnessed a steady rise of political distrust over the past decades, which coincides with the rise of mass immigration. Building on existing research regarding anti-immigration attitudes and political trust, this study presents two possible theoretical mechanisms through which actual immigration trends could generate political distrust in host societies: either through cultural change or through negative evaluations of institutional performance. To empirically test these, I employ a multi-level comparative longitudinal research design using micro-attitudinal data from the European Social Survey for 17 European countries (2002–16). The results do not find support for the cultural hypothesis, as there is no evidence of an overall relationship between growth in foreign populations and citizen distrust in political institutions. However, there is support for the institutional performance hypothesis, whereby growth in foreign populations is associated with higher political distrust amongst individuals who have anti-immigration attitudes. The implication of these findings is that mass immigration is not the central cause of the decline of political trust Europe, however, it may have been a factor in the growing distrust amongst a relatively small sub-group of citizens.